Remarks on the "Letter of the Patriarch Theophylact to Tsar Peter" in the Context of Certain Byzantine and Slavic Anti-heretic Texts - Minczew, Georgi; Majer, Marek (Studia Ceranea, 2013)
The Letter of patriarch Theophylact to tsar Peter is the oldest, but seemingly not the most informative Greek source for the history of Bogomilism. It is in essence a standard document, a typical product of the patriarch’s chancery; it is not conceived as an in-depth investigation into the theological minutiae pertaining to the cosmogony, dogmas and social doctrines of the heretics and the orthodox Church, but rather as a practical tutorial on how to thwart any given neo-Manichaean dualist heresy. It brings to light the fact that Bogomilism, the ‘new’ heresy was treated as an ‘old’ one – as a ‘reactivation’ of earlier gnostic-dualist and neo-Manichaean movements. The letter also features a peculiar innovative feature, though not one directly related to the Bogomil heresy itself: the degree of commitment to preaching the dogmas of the heresy is used for differentiating the situation of the followers. The analysis of the Letter of patriarch Theophylact to tsar Peter raises the more general issue concerning the detailed study of Byzantine and Slavic liturgical texts as a source of information on neo-Manichaean doctrines.